The Association Between Government Health Care Spending and Maternal Mortality in the European Union, 1981 to 2010: A Retrospective Study. Issue 2 (June 2016) - Maruthappu, M.; Ng, K.Y.B.; Williams, C.; Atun, R.; Agrawal, P.; Zeltner, T.
Abstract : ( BJOG . 2015;122(9):1216–1224) Government health care expenditure per capita, on a national level, is a predictor of maternal mortality, which the authors of this study defined as death of a woman during pregnancy, childbirth, or within 42 days of delivery from obstetric causes. In turn, maternal mortality is commonly used as a marker for the performance of a country's health care system. In the present study, authors determined associations between decreases in government health care spending and maternal mortality over a 30-year period (1981 to 2010) in 24 European Union countries, with the goal of elucidating the impact of government health care spending on survival in the parturient population.